A Radish Basic Helix-Loop-Helix Transcription Factor, RsTT8 Acts a Positive Regulator for Anthocyanin Biosynthesis - Lim, Sun-Hyung; Kim, Da-Hye; Kim, Jae K.; Lee, Jong-Yeol; Ha, Sun-Hwa (Frontiers in Plant Science, 2017)
The MYB-bHLH-WDR (MBW) complex activates anthocyanin biosynthesis through the transcriptional regulation. RsMYB1 has been identified as a key player in anthocyanin biosynthesis in red radish (Raphanus sativus L.), but its partner bHLH transcription factor (TF) remains to be determined. In this study, we isolated a bHLH TF gene from red radish. Phylogenetic analysis indicated that this gene belongs to the TT8 clade of the IIIF subgroup of bHLH TFs, and we thus designated this gene RsTT8. Subcellular localization analysis showed that RsTT8-sGFP was localized to the nuclei of Arabidopsis thaliana protoplasts harboring the RsTT8-sGFP construct. We evaluated anthocyanin biosynthesis and RsTT8 expression levels in three radish varieties (N, C, and D) that display different red phenotypes in the leaves, root flesh, and root skins. The root flesh of the C variety and the leaves and skins of the D variety exhibit intense red pigmentation; in these tissues, RsTT8 expression showed totally positive association with the expression of RsMYB1 TF and of five of eight tested anthocyanin biosynthesis genes (i.e., RsCHS, RsCHI, RsF3H, RsDFR, and RsANS). Heterologous co-expression of both RsTT8 and RsMYB1 in tobacco leaves dramatically increased the expression of endogenous anthocyanin biosynthesis genes and anthocyanin accumulation. Furthermore, a yeast two-hybrid assay showed that RsTT8 interacts with RsMYB1 at the MYB-interacting region (MIR), and a transient transactivation assay indicated that RsTT8 activates the RsCHS and RsDFR promoters when co-expressed with RsMYB1. Complementation of the Arabidopsis tt8-1 mutant, which lacks red pigmentation in the leaves and seeds, with RsTT8 restored red pigmentation, and resulted in high anthocyanin and proanthocyanidin contents in the leaves and seeds, respectively. Together, these results show that RsTT8 functions as a regulatory partner with RsMYB1 during anthocyanin biosynthesis.